(untitled) (American Journal of Economics and Business Innovation, 2025)
This study investigates the primary factors affecting Pasig City’s Spanish fine dining restaurants in acquiring millennial customers. It addresses two main questions: which marketing initiatives and dining experiences most influence millennial patronage, and how brand persona mediates the relationship between these elements and customer acquisition. Data were collected from 400 respondents aged 29 to 44 residing in Pasig City through convenience sampling and analyzed using PLS-SEM in WarpPLS 8.0. The results show that millennial acquisition is significantly enhanced by experiential marketing and store atmosphere, with brand persona mediating these effects. In contrast, loyalty programs and digital presence have negligible impacts. A key limitation of this study is its use of non-probabilistic convenience sampling, which, while efficient, limits sample representativeness and reduces the generalizability of findings beyond millennials in Pasig City. In cultural context, the study proposes that brands should integrate brand identity narratives with experiences to align with millennial values. This targeting strategy enables firms in metropolitan areas to address the needs of an underutilized demographic and retain them as customers. Spanish fine dining restaurants can improve their appeal and retention among this demographic through strong storytelling, immersive ambience, exceptional service, and effective marketing in competitive urban areas.